A Plasma System for Low-Emissive Coating Deposition; 7 International conference on modification of materials with particle beams and plasma flows - Ananyin P. S.; Asainov O. Kh. Oleg Khaydarovich; Bainov D. D. Dashi Dambaevich; Bleykher (Bleicher) G. A. Galina Alekseevna; Zhukov V. V.; Zorkalcev A. A.; Krivobokov V. P. Valery Pavlovich; Kosicin L. G.; Legostayev V. N.; Merkulov S. V.; Mikhailov M. N.; Nechaev M. A.; et al. (Coating deposition, 2004)
Title from the title-page.